2014
DOI: 10.1208/s12249-014-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Design and Prepare Solid Dispersions of Poorly Water-Soluble Drug

Abstract: The objective of the present study was to define a systematic approach to design and prepare solid dispersions of poorly water-soluble drug. The systematic approach can be defined in four phases. In the first phase, glass forming ability is assessed, and in the second phase, probable excipients are screened. The screened excipients are evaluated (third phase) for glass transition temperatures (Tg) and miscibility studies according to Florey-Huggins interaction parameter. The predicted excipients are used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…As per these evaluations, it was concluded that the sample of CIL received was crystalline, polymorphic form A (30,31,34). The purity for CIL was 99.3%.…”
Section: Characterization Cil Receivedmentioning
confidence: 95%
“…As per these evaluations, it was concluded that the sample of CIL received was crystalline, polymorphic form A (30,31,34). The purity for CIL was 99.3%.…”
Section: Characterization Cil Receivedmentioning
confidence: 95%
“…Quickly water soluble carrier dissolved rapidly and exposes the drug particles with increased surface area and augments the rate of dissolution. Selection of a carrier is an important step for preparing solid dispersion since the physical stability of the dispersion depends on the miscibility of drug with carrier matrix (5).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study the amorphous 95 form of Td was obtained using several commercially available 96 amorphization techniques [25]. As a result of its relatively high 97 glass transition point (T g ), which is 147°C, Td can be considered 98 as a good glass former in conjunction with its melting point (T m ) 99 at 302°C, with the T g /T m ratio equal to 0.73 [22]. However, Td on 100 its own showed poor physical stability upon contact with water 101 and crystallized immediately, resulting in a quick return to ther-102 modynamic solubility.…”
mentioning
confidence: 99%